Rennie [videorecording (DVD)] - Dressler, Jessica; Klenke, Jen Frank; Anyanwu, Chioma; Davis, Vanessa; MacKey, Valerie; Warner, Camryn (Random Media, 2025)
A hilarious voyeuristic look into a found family of eccentrics working to save their small town's Renaissance Festival. Our Rennies reveal that everyone discovers who they are in a place where one pretends to be something they are not.